Analysis of Willingness to Pay for the Use of Traditional Medicines during the Covid-19 Pandemic in the Village Community of Kiringan Canden, Bantul - Listiana Hidayati (Majalah Farmaseutik, 2022)
When the Corona virus infects the body, eating will cause the body's reaction to build the body's ability to eradicate the virus. If the immune system is strong, the virus will die and vice versa with a weak immune system, it will be reversed by the immune system and can trigger severe symptoms and fatal complications. Immunostimulants can enhance specific and non-specific body defense mechanisms, and there is non-specific induction of both cellular and humoral defense mechanisms. Traditional medicine is used to relieve the symptoms of COVID-19. There are no studies that show this treatment can prevent or cure the disease caused by COVID-19. The purpose of this study was to determine the characteristics of consumers of traditional medicine and the value of willingness to pay (WTP) for traditional medicines in the hamlet of Kiran, Bantul, Yogyakarta. This study uses a non-experimental descriptive analytical method through the distribution of questionnaires. The research was conducted in Kringan Hamlet, Bantul, Yogyakarta with purposive sampling method. The number of samples used was 276 respondents. Primary data were then analyzed descriptively and Contingent Valuation Modeling (CVM). The results showed the characteristics of the respondents, namely the distribution according to age as many as 69 respondents aged 36-45 years (25%), the dominant gender was 156 respondents (57%), the level of education was mostly high school as many as 137 respondents (50%) and the level of education was high school. the highest income of 172 respondents (62%) is < Rp 1 million. The average WTP value of ginger is Rp. 19,822.46 or the total WTP value is Rp. 6,280,434.78, the average value of WTP of ginger is Rp. 10,956.52 or the total value of WTP is Rp. 5,175,000.00, the average value of WTP of lemongrass is Rp. 10,140.51 or the total value of WTP is IDR 5,445,978.26, while the average value of WTP for lemongrass is IDR 9,583.33 or the total value of WTP is IDR 10,733,478.26